Characterization of urinary metabolites as biomarkers of colistin-induced nephrotoxicity in rats by a liquid chromatography/mass spectrometry-based metabolomics approach. (25th April 2016) - Jeong, Eun Sook; Kim, Gabin; Moon, Kyoung-Sik; Kim, Yong-Bum; Oh, Jung-Hwa; Kim, Ho-Sook; Jeong, Jayoung; Shin, Jae-Gook; Kim, Dong Hyun
Highlights: Urinary metabolic profiles were assessed in rat after treatment of colistin methane sulfonate. Urinary amino acids and creatine levels were significantly increased whereas levels of purine metabolites and metabolites related to the tricarboxylic acid cycle were reduced. Concentrations of colistin in kidney were higher than those in liver. Colistin may cause tubular damage, leading to increased urinary levels of metabolites. Abstract: Colistin is a polypeptide antibiotic that effectively treats infections caused by multidrug-resistant Gram-negative bacteria, but its clinical use is limited due to nephrotoxicity. The purpose of the present study was to identify biomarkers of colistin-induced nephrotoxicity and to further characterize the mechanisms underlying this process by analyzing urinary metabolites using untargeted metabolomic approach. Rats receiving intraperitoneal administration of colistin sodium methanesulfonate (CMS) (25 or 50 mg/kg) exhibited histopathological changes in the kidney and increased blood urea nitrogen levels. Additionally, the levels of phenylalanine, tryptophan, and tyrosine in the urine of the CMS-treated group were significantly higher than those of the control group, suggesting that colistin caused proximal tubular damage. Urinary acetylcarnitine and butyrylcarnitine levels also increased after CMS treatment, but the levels of purine metabolites and metabolites related to the tricarboxylic acid cycle were reduced. The most significant increase in the CMS-treated groups was observed in creatine levels. CMS-induced selective nephrotoxicity may be attributed to relatively high tissue concentrations of colistin in the kidney. Taken together, our results indicate that high levels of colistin in the kidney caused perturbations in the tricarboxylic acid cycle, amino acid metabolism, creatine metabolism, and purine metabolism and ultimately led to kidney injury.